t-BuONa-Mediated Transition-Metal-Free Autoxidation of Diarylmethanes to Ketones - Li, Jiang-Sheng; Yang, Fan; Yang, Qian; Li, Zhi-Wei; Chen, Guo-Qin; Da, Yu-Dong; Huang, Peng-Mian; Chen, Chao; Zhang, Yuefei; Huang, Ling-Zhi (Synlett, 2017)
Autoxidative sp3 C–H transformation of diarylmethanes has been demonstrated using O2-mediation by t-BuONa. This protocol enables an alternative route for the access to diaryl ketones from benzyl derivatives in good to excellent yields under mild reaction conditions, without transition metal catalysts or additional chemical oxidants.
Keywords: Ketones; benzyl derivatives; autoxidation; metal-free; oxygenation